Towards Economic Resilience and Food Security: Leveraging Livelihood Capital and Technology for Farmer Adaptation in East Java, Indonesia - Bunga Hidayati; Eko Setiawan; Fitri Candra Wardana; Dini Atikawati; Maharani Pertiwi (Jurnal Ekonomi dan Studi Pembangunan, 2025)
The agricultural sector's contribution in East Java Province has diminished, primarily due to the prevalence of traditional farming practices, reliance on climate variability, and limited adoption of modern technology. These challenges result in seasonal poverty and heightened vulnerability for many farmers, impacting their economic resilience and food security. This study examines the impact of various livelihood assets on farmers' adaptive capacities in East Java, utilizing Structural Equation Modelling-Partial Least Squares (SEM-PLS) to explore both direct and indirect relationships between livelihood capital and adaptation levels. The findings reveal that livelihood capital significantly enhances farmers' adaptive capacities directly and indirectly. Moreover, strong livelihood capital contributes positively to farmers’ resilience to climate change, thus promoting food security in the region. These results underscore the crucial role of bolstering livelihood capital as an effective strategy to enhance farmers' adaptive capacity and address vulnerability challenges, ultimately supporting food security.